Improvements in Aircraft Gas Turbine Engines for the 90s - Prasad, Arun (Defence Science Journal, 2013)
The gas turbine propulsion system has been playing the most significant role in the evolution and development of present-day aircraft, and has become the limiting technology for developing most new aircraft. However, the jet engine still remains the preferred propulsion choice. Aircraft gas turbines in one form or the other, viz. turbojet, turbofan, turboprop or turboshaft, have been used in commercial passenger aircraft, high performance military aircraft and in rotary wing aircraft (helicopters). The emphasis in engine development programmes world over seems to be in reducing fuel consumption, increasing thrust and in reducing weight.